2010
DOI: 10.1002/mnfr.200900467
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of jejunal induction of the maltase–glucoamylase gene by a high‐starch/low‐fat diet in mice

Abstract: Maltase and glucoamylase are derived from the same mRNA and are responsible for digestion of starch in the small intestine. Their jejunal activities in rodents are induced by a high-starch/low-fat (HS)-diet. However, it is unknown whether jejunal expression of the maltase-glucoamylase (Mgam) gene is enhanced by the HS-diet. In this study, we found that jejunal Mgam mRNA was increased by a HS-diet in mice. We showed that the HS-diet increased acetylation of histones, bindings of a coactivator, Creb binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
(43 reference statements)
2
28
0
Order By: Relevance
“…One potential factor is diet. Dietary intake of carbohydrates can regulate the mRNA expression of disaccharidases and hexose transporters in mice and rats [43], [44], [45]. Several studies suggest that ASD children exhibit feeding selectivity and aberrant nutrient consumption [46], [47], [48], [49], [50], [51], [52].…”
Section: Discussionmentioning
confidence: 99%
“…One potential factor is diet. Dietary intake of carbohydrates can regulate the mRNA expression of disaccharidases and hexose transporters in mice and rats [43], [44], [45]. Several studies suggest that ASD children exhibit feeding selectivity and aberrant nutrient consumption [46], [47], [48], [49], [50], [51], [52].…”
Section: Discussionmentioning
confidence: 99%
“…Because changes in mass-specific activities of carbohydrases and aminopeptidase-N in our experiment differed in both direction and magnitude (Fig.3), we hypothesize that observed diet effects were probably mediated by site-specific changes in the rate of synthesis or degradation of carbohydrases. Studies in rodents revealed several genetic and molecular mechanisms that can be responsible for such changes (Takase and Goda, 1990;Shinohara et al, 1993;Kishi et al, 1999;Goda, 2000;Honma et al, 2007;Tanaka et al, 2008;Mochizuki et al, 2010a;Mochizuki et al, 2010b). We cannot pinpoint the mechanisms that were responsible for dietary modulation of intestinal carbohydrase activities observed in our experiment.…”
Section: Molecular Basis For Observed Dietary Modification Of Intestimentioning
confidence: 69%
“…Metabolic change in humans is evident as reduced adipose tissue lipolysis [15], increased uptake of glucose into skeletal muscle [15], reduced triglyceride storage within muscle [16 & ], increased uptake of SCFA into both muscle and adipose [15], and increased meal fat oxidation. Additionally, in animal models as reduced lipogenic enzyme [14] and lipogenesis in adipose tissue [26], reduced adipocyte size [27], increased hepatic fatty acid oxidation [22] and upregulation of fatty acid catabolism-related liver enzymes [22]. Many of these effects are likely to be directly or indirectly related to the SCFA produced following fermentation.…”
Section: Resistant Starch and Insulin Sensitivitymentioning
confidence: 95%
“…Zhu et al [13] investigated the effects of a high-amylose rice (HA2 transgenic rice) compared to a wild-type; however, there was no effect on fasting glucose or insulin levels after 4 weeks (postprandial data not measured). Recent work in rat models documented a reduction in jejunal alpha-glucosidase activity following 2-week feeding of maize-resistant starch [14] which might explain lower postprandial glucose digestion and absorption of the available CHO portion when resistant starch is present, although the effects of starch source and the mechanism underlying this effect are unknown. How does this compare to work from humans?…”
Section: Chronic Effects Of Resistant Starch On Glucose Controlmentioning
confidence: 97%